A Case of Lymphomatoid Papulosis Type E With an Unusual Exacerbated Clinical Course. (February 2018) - Belousova, Irena E.; Kyrpychova, Liubov; Samtsov, Alexey V.; Kazakov, Dmitry V.
Abstract : Abstract: Lymphomatoid papulosis (LyP) type E is a recently delineated variant characterized by the occurrence of large necrotic "eschar"-like lesions displaying microscopically angioinvasive and angiodestructive infiltrates composed of CD30 + lymphocytes, frequently coexpressing CD8. In contrast to other LyP variants where patients develop multiple lesions, most patients with LyP type E present with few lesions (often 1 or 2 at a given time). In this article, we describe a 34-year-old man with LyP type E with an exacerbated clinical course characterized by the occurrence of almost a hundred of lesions. Initially, he presented with a single rapidly growing 2-cm large erythematous nodule on the forearm but after the administration of doxycycline multiple eschar-like lesions developed all over the body. Atypical lymphoid infiltrates with marked angiocentricity and angiotropism of CD30 + medium-sized to large pleomorphic lymphocytes were seen histopathologically. After the withdrawal of the antibiotic, the lesions spontaneously regressed. Awareness of this rare LyP variant and its correct recognition, even if the clinical course is unusual and worrisome, is important to avoid aggressive treatment.